PRMT5 as a druggable target for glioblastoma therapy. Issue 6 (2nd November 2017) - Banasavadi-Siddegowda, Yeshavanth Kumar; Welker, Alessandra M; An, Min; Yang, Xiaozhi; Zhou, Wei; Shi, Guqin; Imitola, Jaime; Li, Chenglong; Hsu, Sigmund; Wang, Jiang; Phelps, Mitch; Zhang, Jianying; et al.
Abstract: Background: In spite of standard multimodal therapy consisting of surgical resection followed by radiation and concurrent chemotherapy, prognosis for glioblastoma (GBM) patients remains poor. The identification of both differentiated and undifferentiated "stem cell like" populations in the tumor highlights the significance of finding novel targets that affect the heterogeneous tumor cell population. Protein arginine methyltransferase 5 (PRMT5) is one such candidate gene whose nuclear expression correlates with poor survival and has been reported to be required for survival of differentiated GBM cells and self-renewal of undifferentiated GBM cells. In the current study we screened the specificity and efficacy of 4 novel PRMT5 inhibitors in the treatment of GBM. Methods: Efficacies of these inhibitors were screened using an in vitro GBM neurosphere model and an in vivo intracranial zebrafish model of glioma. Standard molecular biology methods were employed to investigate changes in cell cycle, growth, and senescence. Results: In vitro and in vivo studies revealed that among the 4 PRMT5 inhibitors, treatment of GBM cells with compound 5 (CMP5) mirrored the effects of PRMT5 knockdown wherein it led to apoptosis of differentiated GBM cells and drove undifferentiated primary patient derived GBM cells into a nonreplicative senescent state. Conclusion: In vivo antitumor efficacy combined with the specificity of CMP5 underscores the importance of developing it for translation.